Frequency of Complete Heart Block in Patients Presenting with Acute St-Segment Elevation Myocardial Infarction (STEMI) - Abdullah, Shahzad; Latif Ullah; Muhammad Alam; Ahmad, Sohail (Indus Journal of Bioscience Research, 2025)
Background: Acute ST-segment elevation myocardial infarction is one of the most serious type of heart attack where blood flow to part of heart muscle stop suddenly due to blockage of coronary artery, mostly by a clot forming on a ruptured plaque. It causes severe chest pain, sweating, and breath difficulty and need quick treatment to save life. Complete heart block is a serious complication in such patients, happen when the electrical signal from upper to lower chamber stop passing. This lead to very slow heart rate and can cause fainting or death if not managed quickly. Objective: To determine the frequency of complete heart block in patients presenting with Acute ST-Segment Elevation Myocardial Infarction STEMI to a tertiary care hospital. Study Design: Cross-sectional descriptive study. Duration and Place of Study: Conducted from September 2024 to March 2025 in the Department of Cardiology, Saidu Group of Teaching Hospital, Swat. Methodology: A total of 237 patients aged 18–70 years diagnosed with ST-segment elevation myocardial infarction were included by consecutive sampling. Diagnosis was based on chest pain, ECG changes, and raised cardiac biomarkers. Complete heart block was diagnosed when P waves and QRS complexes were independent on ECG. Results: Out of 237 patients, 169 (71.3%) were males. The mean age was 48.68±12.69 years. Complete heart block was found in 36 patients (15.20%). No significant association was found with age, gender, BMI, pain duration, residence, or comorbidities (p>0.05). Conclusion: This study has concluded that complete heart block is not rare in patients presenting with acute ST-segment elevation myocardial infarction and show serious clinical concern, mostly due to ischemic damage and treatment delay.